Acute liver failure due to radiographically occult infiltration of urothelial cancer - Tosatto, Valentina (2021)
Introduction: Acute liver failure (ALF) due to diffuse infiltrating solid malignancy without any focal lesions on radiographic imaging is rare. Case report: A 70-year-old man was admitted due to mental confusion, abdominal pain, and ALF. Three years before, he had undergone a left nephrectomy for urothelial carcinoma followed by adjuvant chemotherapy. The abdominal computed tomography (CT) showed hepatomegaly and ascites. Ascitic fluid had transudate characteristics, with no malignant cells. Percutaneous liver biopsy (LB) showed diffuse liver infiltration of metastatic urothelial carcinoma. The patient rapidly deteriorated and died in a week due to ALF. Discussion: History of solid cancer and hepatomegaly and/or liver failure without other obvious explanation should encourage to perform LB. Conclusion: LB is warranted to avoid misdiagnosis, prolonged hospital stays, and delay in palliative care.